THE RELATIONSHIP BETWEEN HERBAL MEDICINE CONSUMPTION IN POSTPARTUM MOTHERS AND THE INCIDENCE OF DIARRHEA IN INFANTS AGED 7-40 DAYS AT THE BULANGAN HAJI HEALTH CENTER, PAKONG SUB-DISTRICT, PAMEKASAN. - Rahmawati, Sylvina; Rohemah, Rohemah; Purmahardini, Nova; Dian, Iva Gamar; Lianita, Pun (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
Jamu Nifas is a traditional herbal medicine that is made from the original recipe of the ancestors of Madura, from herbal plants. The purpose of this study was to determine the relationship of herbal medicine consumption in postpartum women with the incidence of diarrhea in infants aged 7-40 days. The type of research used was correlation analytic with a cross sectional approach, the population of postpartum mothers who had babies was 41, the sample was determined according to simple random sampling as many as 38 postpartum mothers who had babies, using the independent variable of herbal medicine consumption in postpartum mothers and the dependent variable of diarrhea incidence in infants aged 7-40 days. Using Fisher's Exact Test statistical test at the degree of significance Î± = 0.05.The results showed that almost all (92.3%) of the 24 mothers who consumed herbal medicine had diarrhea. The results of the Fisher's Exact Test statistical test show the value (Ï) = 0.000 <0.05, then H0 is rejected, meaning that there is a relationship between the consumption of herbal medicine in postpartum mothers with the incidence of diarrhea in infants aged 7-40 days. Based on the results of the study, it is concluded that mothers who consume herbal medicine during the postpartum period can cause diarrhea in infants. Because of the hygine factor that is less clean and the content of spices that are too hot. In order to minimize the factors that cause babies to experience diarrhea, mothers should not carelessly consume food and drinks, especially in choosing traditional herbs that do not harm mothers and babies. If you want to consume herbal medicine, you should precipitate it first and then drink it clearly.Â Â